Polarization dependence of microwave-induced magnetoconductivity oscillations in a two-dimensional electron gas on liquid helium - Monarkha, Yu.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
The dependence of radiation-induced dc magnetoconductivity oscillations on the microwave polarization is theoretically studied for a two-dimensional system of strongly interacting electrons formed on the surface of liquid helium. Two different theoretical mechanisms of magnetooscillations (the displacement and inelastic models) are investigated. We found that both models are similarly sensitive to a change of circular polarization, but they respond differently to a change of linear polarization. Theoretical results are compared with the recent observation of a photoconductivity response at cyclotron-resonance harmonics.